2021
DOI: 10.3390/ijerph18042033
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Environmental Dynamism Promotes Entrepreneurial Team Member’s Innovation: Explanations Based on the Uncertainty Reduction Theory

Abstract: This study aims to examine the effect of perceived environmental dynamism on entrepreneurial team member’s innovation. Based on the uncertainty reduction theory, this study constructs a multilevel moderated mediation model of the relationship between perceived environmental dynamism and entrepreneurial team member’s innovation. By collecting questionnaires from 117 entrepreneurial team leaders and 479 team members in China, this research found that perceived environmental dynamism could stimulate entrepreneuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 48 publications
1
67
0
3
Order By: Relevance
“…The innovation and entrepreneurship education activities in colleges and universities have achieved some fruitful results. However, to reinforce college students' values, innovation and entrepreneurship education must be strengthened continuously; this is consistent with the findings of Deng et al ( 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…The innovation and entrepreneurship education activities in colleges and universities have achieved some fruitful results. However, to reinforce college students' values, innovation and entrepreneurship education must be strengthened continuously; this is consistent with the findings of Deng et al ( 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Higher TMD scores represent more obvious negative moods (Zhu, 1995 ). It has been shown that the Simplified POMS is a useful tool to investigate emotional status based on numerous experiments (Zhu, 1995 ; Wang and Lin, 2000 ; Deng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our finding is consistent with Upson et al (2017), who used data collected from women entrepreneurs in India. They suggested that entrepreneurs that operate in "discovery" contexts tend to participate in homogeneous networks, while entrepreneurs in "creation" contexts tend to participate in heterogeneous networks (Deng and Chen, 2021).…”
Section: Major Findingsmentioning
confidence: 99%